1978
DOI: 10.1159/000198228
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Function in Inflammatory Bowel Disease

Abstract: Pulmonary function has been assessed in patients with ulcerative colitis and Crohn’s disease and compared with a healthy population. No statistically significant differences were found in the measurements observed within the three groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 4 publications
2
17
0
Order By: Relevance
“…JOHNSON et al [13] and HEATHLEY et al [11] failed to find a significant correlation between elevated CIC levels and pulmonary abnormalities. The role of circulating intestinal endotoxins [24] and/or excessive discharge of protease from inflammatory areas has also been described.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…JOHNSON et al [13] and HEATHLEY et al [11] failed to find a significant correlation between elevated CIC levels and pulmonary abnormalities. The role of circulating intestinal endotoxins [24] and/or excessive discharge of protease from inflammatory areas has also been described.…”
Section: Discussionmentioning
confidence: 98%
“…Some authors found no difference in pulmonary function data in patients with inflammatory bowel disease and control groups [13,14]. HEATLEY et al [11] found abnormal lung function in about 50% of 102 patients with inflammatory bowel disease, including Crohn's disease and ulcerative colitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since its first report, abnormal pulmonary function tests (PFTs) have been reported in 17–55% patients with UC,2, 3, 4, 5, 6 including a decrease in gas transfer factor (diffusion lung capacity for carbon monoxide [DLCO]),7, 8 elevated functional residual capacity (FRC),9 decrease in maximal mid‐expiratory flow rate (MEFR),10 or an increased frequency of bronchial hyperresponsiveness11; however, in some studies, no abnormalities in PFT were found 10, 12. Various respiratory abnormalities reported in patients with UC include obstructive and interstitial lung disease,13 small and large airway disorders,14, 15 increase in bronchial sensitivity,11 bronchitis, bronchiectasis,16, 17 and bronchiolitis oblitrans 18.…”
Section: Introductionmentioning
confidence: 99%
“…Respiratory symptom prevalence ranges from 25.6% in a recent study of 30 UC and 9 CD patients to 50% in an older study of 11 Decreased forced expiratory volume in the 1 st second (FEV1), decreased FEV1/forced vital capacity (FVC) ratio, increased residual volume (RV)/total lung capacity (TLC) ratio, low forced expiratory flow (FEF25-75) and, more importantly, decreased DLCO are the parameters noted to be abnormal in IBD patients in the existing literature. While FEV1 and FEV1/FVC ratio have been found to be normal in certain older studies, other studies and recent data suggest mild functional compromise [33,34] . Results should be interpreted with caution since different criteria have been used to define abnormal and certain studies included smoking patients or an inappropriate control population.…”
Section: Symptoms -Clinical Examinationmentioning
confidence: 89%